Exploration des facteurs influençant l’adoption du Mobile Banking au Maroc - EL HALOUI , Yassine; ALJ , Bouchra (Revue Internationale du Chercheur, 2023)
Morocco is relying on mobile banking to develop the financial inclusion of its population and thus reduce disparities in terms of access and use of formal financial services between different social groups. Mobile banking represents one of the main pillars of the National Strategy for Financial Inclusion initiated by regulator Bank Al Maghrib. In view of its advantages over so-called "traditional" banking offers, it is important to identify the factors that can ensure its diffusion. The aim of this article is to identify the most relevant theoretical models in relation to the adoption of mobile banking and empirically measure the influence of the main variables incorporated in these models, based on the responses of a sample of 144 unbanked people with an M-wallet account. The literature review enabled us to observe that the theoretical models relating to the adoption of mobile banking present similarities in terms of the explanatory variables retained. From an empirical point of view, our study revealed that mobile banking adoption is influenced by perceived comparative advantage and perceived ease of use, while perceived trust plays a minimal role.